Budaya Politik Warga Nahdlatul Ulama Kota Bandar Lampung: Belajar dari Pencalonan Ma’ruf Amin dalam Pemilihan Umum 2019 - Ahmad Robi Ulzikri; Robi Cahyadi Kurniawan; Himawan Indrajat (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2021)
This research is motivated by the involvement of the highest leadership (rais aam) of the Nahdlatul Ulama (PBNU) Executive Board Ma'ruf Amin who was appointed as a vice presidential candidate to accompany the incumbent Joko Widodo in the 2019 general election. Research problems arise when the public doubts the solidity between structural elements. NU and NU cultural elements (village kiai and Islamic boarding schools), including in Bandar Lampung. So, the purpose of this research is to find out how the political culture of the NU residents of Bandar Lampung city from the structural and Islamic boarding schools in the momentum of the Presidential and Vice Presidential Election in 2019. This research is analyzed using the political culture theory of Gabriel Almond and Sidney Verba. The combined research method with the model is concurrent embedded used in this study, which is a research method that combines qualitative and quantitative approaches where qualitative data is more dominant. The results of this study indicate that: first, the type of structural citizen political culture of NU is participant political culture, because it has cognition, affection, and evaluation of all aspects including the system as a general object, objects of input and output, and the person as an object in the system. in the context of the Presidential and Vice-Presidential Election in 2019. The second result, NU cultural residents from the kiai and Islamic boarding school students have a cultural type of transition from subject to participant, this is because this group has a good assessment of input objects, but still has a deficiency in individual participation. A number of factors that influence the political culture of both include the level of education, character, and values ??that guide both of them in their actions. The results of research with a political culture approach can be concluded that elements of structural NU and cultural NU in Bandar Lampung have solidity in winning the pair Joko Widodo and Ma'ruf Amin in the 2019 Election